THE USE OF POLITENESS PRINCIPLES IN LOOK AHEAD AN ENGLISH COURSE FOR SENIOR HIGH SCHOOL STUDENTS YEAR XI WRITTEN BY TH. M. SUDARWATI AND EUDIA GRACE - Haryono, Purwo; ., Rustinaningsih (MAGISTRA, 2013)
The paper aims at describing the use of politeness principles which are found in the utterances in Look Ahead An English Course for Senior High School Students Year XI written by Th. M. Sudarwati and Eudia Grace. The data are collected by note taking and observing the texts and then analyzed by descriptive qualitative method. After analyzing the data, the writers find 16 uses of politeness principles, they are one tact maxim, four generosity maxims, two approbation maxims, one modesty maxim, four agreement maxim, and four sympathy maxims. There can be found nine obedience and denial of maxim, they consist of one obeying tact maxim and denying modesty maxim, four obeying generosity maxim and denying approbation maxim, two obeying approbation maxim and denying modesty maxim, one obeying approbation maxim and denying agreement maxim, and one obeying agreement maxim and denying approbation maxim. Key words: politeness principle, text book, utterance, maxim.